Ergodic capacity of correlated multiple-input–multiple-output channel with impact of transmitter impairments - Abdullah Mohammed Auday; Al-Masoody Wasan Hashim Jacob (Open Engineering, 2022)
The ergodic capacity of the ideal multiple-input and multiple-output (MIMO) channel grows unboundedly at the-high SNRs because of the assumption that the transceivers used in the system do not affect the signal that passes through them. In reality, the transceivers used in the MIMO system suffer from many impairments such as phase noise, quantization noise, and non-linear amplifier. These physical transceivers will affect the signal that passes through them. Thus, the influence of the physical transceivers cannot be neglected in the analysis of the MIMO channel capacity. Additionally, another essential thing that must be considered when analyzing the MIMO channel capacity is the correlation between the channel elements. Therefore, to get results close to the behavior of the practical results for the capacity of any MIMO system, this article proposes an algorithm that simulates the capacity of the correlated MIMO channel that suffers from Rayleigh flat fading with the presence of the physical transmitter. This work is done by considering that the effect of the physical transmitter at the nth transmitting antenna is a Gaussian distortion noise with a zero mean and variance proportional to the power of the signal transmitted through the same antenna. The simulation process for the proposed technique is manipulated by MATLAB software with 10,000 realizations of the channel. Also, the transmitter impairment thresholds employ in the simulation are 0.08 and 0.175. The simulation results showed that the channel capacity with the physical transmitter stopped growing at a specific limit in the very high-SNRs, and it decreased at the medium and high SNRs when the correlation coefficient increased.